Penerapan Media Tutorial untuk Meningkatkan Kualitas Pembelajaran Di SMK Negeri 7 Pangkep - HM, Setiawan; Kadirman, Kadirman; Nur, Hasanah (Jurnal Pendidikan Teknologi Pertanian, 2020)
This research is a Class Action Research which aims to improve the quality and learning outcomes of students. The purpose of this study was to improve the learning outcomes of Agribusiness XI grade students of State Vocational High School 7 Pangkep with tutorial media on traditional fishery product processing subjects and to determine the effect of using media tutorials in learning. The subject of this study consisted of 28 students. Data collection techniques used are observation and giving tests at the end of each cycle in accordance with the material being taught. The research procedure includes stages: (a) planning, (b) implementation, (c) observation, and (d) reflection. The collected data were analyzed using qualitative and quantitative data. Based on the results of the study, it can be concluded that the use of tutorial media can improve student learning outcomes. This is evident in the pre test, cycle I and cycle II student learning outcomes have increasedKeywords: Media, Learning Outcomes, Qualitative, Quantitative